1998
DOI: 10.1098/rspb.1998.0351
|View full text |Cite
|
Sign up to set email alerts
|

MHC-genotype of progeny influenced by parental infection

Abstract: In a previous series of in vitro fertilization experiments with mice we found non-random combination of major histocompatibility complex (MHC) haplotypes in the very early embryos. Our results suggested that two selection mechanisms were operating: (i) the eggs selected speci¢c sperm; and (ii) the second meiotic division in the eggs was in£uenced by the type of sperm that entered the egg. Furthermore, the proportion of MHC-heterozygous embryos varied over time, suggesting that non-random fertilization was depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 46 publications
3
77
0
Order By: Relevance
“…Thus, the observed mate compatibility, which explains roughly 44% of the variation in sperm velocity (42-45% across models), appears to be characterized by factors other than MHC, potentially by other peptides identified in the ovarian fluid of Chinook salmon (Johnson et al, 2014). MHC-dependent fertilization success was reported in mice (Wedekind et al, 1996;Rülicke et al, 1998) and the red jungle fowl (Løvlie et al, 2013), but the mechanisms by which such a non-random gamete fusion occurs are yet unknown. In this study, we observed an MHC class II-based fertilization success, but our data suggests that this bias is achieved via mechanisms other than MHC-based sperm velocity in ovarian fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the observed mate compatibility, which explains roughly 44% of the variation in sperm velocity (42-45% across models), appears to be characterized by factors other than MHC, potentially by other peptides identified in the ovarian fluid of Chinook salmon (Johnson et al, 2014). MHC-dependent fertilization success was reported in mice (Wedekind et al, 1996;Rülicke et al, 1998) and the red jungle fowl (Løvlie et al, 2013), but the mechanisms by which such a non-random gamete fusion occurs are yet unknown. In this study, we observed an MHC class II-based fertilization success, but our data suggests that this bias is achieved via mechanisms other than MHC-based sperm velocity in ovarian fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, MHC-dependent CFC could also arise after the sperm has entered the egg and before the pronucleus fusion (Yeates et al, 2009). MHC-based CFC was uncovered in the red jungle fowl (Løvlie et al, 2013) and in vitro fertilization experiments in MHC-congenic mice revealed an MHC-dependent gamete fusion (Wedekind et al, 1996;Rülicke et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A number of adaptive hypotheses, which are not necessarily mutually exclusive, have been proposed to explain how MHC could influence mating behaviour and reproductive success. Those that have received most attention are: (1) MHC-related selective fertilisation (Wedekind et al, 1996;Rulicke et al, 1998;Wedekind et al, 2004); (2) MHC-dependent selective abortion (Alberts and Ober, 1993); (3) disassortative matings based on MHC genotype (Penn and Potts, 1999). Here, we focus on the latter, as this has been the primary focus for studies in non-model vertebrates.…”
Section: Mhc-dependent Sexual Selection Mate Choice and The Mhcmentioning
confidence: 99%
“…Under a good-genes model, if females preferentially mate with superior-condition males that are relatively disease resistant, they may provide their offspring with 'good' MHC haplotypes associated with improved resistance to pathogens within the current environment, or avoid 'bad' MHC haplotypes associated with deleterious effects (Abplanalp et al 1992;Wedekind et al 1996;Rulicke et al 1998). In this scenario, males with a greater diversity of MHC alleles should, through either heterozygote advantage or from an increased chance of having specific resistant alleles, be in better condition and, therefore, be preferred by females.…”
Section: Introductionmentioning
confidence: 99%